The Role of Human Development on Deforestation in Africa: A Modelling-Based Approach - Simplice A. Asongu; Brian Jingwa (African Governance and Development Institute (AGDI), 2012)
The rate of deforestation in Africa is of paramount concern not only to the future of Africa, but also to the world. This study uses country-level data to model changes in forest area over an 18 year period (1990-2007) in 35 African countries and investigates the role played by important development indicators of human development. The results reveal that the net loss of forests was 0.19% every year between 1990 and 2007. This implies a total of 3.42% of forest was lost in the 18 year period. This is more in line with estimates obtained by the Food and Agricultural Organization (0.56% between1990-2000 and 0.49% between 2000-2010). Human development which involves life expectancy, education and income is found to have a positive effect on forest growth and conservation, while cutting down trees for wood fuel is a significant cause of deforestation. Using generalized linear mixed models and generalised estimating equations, we were able to calculate expected estimates of forest area for 2010, 2020 and 2030 under the assumption that nothing is done to change observed trends. In many countries, progress has been made in reforestation, forest protection and conservation. However, if indiscriminate cutting down of trees is not checked, many countries will lose most or all of their forests by 2030.
Keywords: C33; C36; C50; O13; Q23; I10; 330; Deforestation; Environment; Human development index; Agriculture; Data modelling; Africa